2019
DOI: 10.1074/mcp.ra119.001507
|View full text |Cite
|
Sign up to set email alerts
|

Canine Bone Marrow-derived Mesenchymal Stem Cells: Genomics, Proteomics and Functional Analyses of Paracrine Factors

Abstract: • Canine bone marrow-derived mesenchymal stem (BMMSC) express genes for differentiation toward osteo-, chondro-, and tendo-genic directions. • Canine BMMSC express genes associated with angiogenic, neurotrophic, and immunomodulatory properties. • Dynamic of BMMSC conditioned medium (CM) proteome revealed transcription and translation factors, osteogenic, growth, angiogenic, and neurotrophic factors. • BMMSC CM express angiogenic activity in the chorioallantoic membrane (CAM) assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
(50 reference statements)
2
24
0
Order By: Relevance
“…For this reason, in the present study we decided to include canine BMMSC, which possess a typical mesenchymal immune profile and multilineage capacity. Furthermore, the standardized procedure for obtaining BMMSC and producing corresponding CM were well defined in our previous comprehensive genomic, proteomic and functional study, confirming their paracrine effect by releasing various pro-regenerative mediators, including chemokines, cytokines, growth and neuroprotective factors, as well as immune-modulatory proteins affecting adaptive and innate cells [ 25 ]. Although, they were differentiated into osteogenic and chondrogenic lineages, low adipogenesis occurred.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For this reason, in the present study we decided to include canine BMMSC, which possess a typical mesenchymal immune profile and multilineage capacity. Furthermore, the standardized procedure for obtaining BMMSC and producing corresponding CM were well defined in our previous comprehensive genomic, proteomic and functional study, confirming their paracrine effect by releasing various pro-regenerative mediators, including chemokines, cytokines, growth and neuroprotective factors, as well as immune-modulatory proteins affecting adaptive and innate cells [ 25 ]. Although, they were differentiated into osteogenic and chondrogenic lineages, low adipogenesis occurred.…”
Section: Discussionmentioning
confidence: 83%
“…However, identifying the optimal cell type candidate with the highest neuroprotective effect is the key condition for successful therapy. According to our genomic, proteomic and functional study, canine bone marrow-derived MSCs seem to be one of the best candidates, since they release a variety of bioactive molecules possessing strong paracrine factors which may affect various neurological disorders [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a comprehensive proteomic determination of the content of canine MSC CM similarly demonstrated the secretion of a wide variety of trophic and immunomodulatory factors [30]. Furthermore, other research has shown that canine bone marrow MSCs secrete neurotrophic factors and angiogenic factors into the conditioned medium, which promoted angiogenesis using the chorioallantoic membrane assay [31]. Transplantation of canine MSCs into dogs with SCI also was associated with their expression of neurotrophic factors in vivo [32] and increased neural regeneration [33] and functional recovery after SCI [33][34][35].…”
Section: Discussionmentioning
confidence: 98%
“…Three out of our six examined cBM MSC CM were submitted to proteomic analyses kindly provided by the Laboratoire Protéomique, Réponse Inflammatoire et Spectrométrie de Masse-PRISM, in France (the results of these proteomic analyses are shown in the research article by Humenik et al [ 19 ], in Supp. Data 1 – List of the proteins identified).…”
Section: Discussionmentioning
confidence: 99%
“…A bone marrow sample collection from six individual healthy adult dogs (large or middle-size dog breeds, all males: Alaskan Malamute (2.0 years old), Labrador (2.3 years old), American Staffordshire Terrier (2.6 years old), Poodle (2.4 years old), Eurohound (2.7 years old), Beagle (2.4 years old)) and in vitro cultivation of cBM MSCs were performed at the University of Veterinary Medicine and Pharmacy in Košice with informed consent of the dog owners, as described in detail by Humenik et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%